2020
DOI: 10.1038/s41598-020-58713-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concurrent right ventricular myocardial infarction on outcomes among patients with left ventricular myocardial infarction

Abstract: to compare in-hospital outcomes between left ventricular myocardial infarction (LVMi) patients with and without right ventricular myocardial infarction (RVMi). patients with acute St-segment elevation Mi (SteMi) undergoing primary percutaneous coronary intervention (pci) were enrolled and divided into LVMI with and without RVMI groups. Between-group differences and in-hospital outcomes were compared. compared to patients without RVMi, patients with RVMi were more likely to be male, have higher body mass index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Morbidity and mortality are well known to be associated with right ventricular (RV) involvement after an acute myocardial infarction (MI). 17 In 50% to 80% postmortem and animal studies, RV involvement in acute MI has been reported but is frequently underestimated in the clinical setting owing to the diagnostic limitations of the electrocardiogram (ECG) and echocardiography. However in this study, we found that right ventricular function measured by TAPSE was not associated with TIMI score as predicted score for 30 days mortality of STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality are well known to be associated with right ventricular (RV) involvement after an acute myocardial infarction (MI). 17 In 50% to 80% postmortem and animal studies, RV involvement in acute MI has been reported but is frequently underestimated in the clinical setting owing to the diagnostic limitations of the electrocardiogram (ECG) and echocardiography. However in this study, we found that right ventricular function measured by TAPSE was not associated with TIMI score as predicted score for 30 days mortality of STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that patients with concomitant RVMI have higher of inhospital complications, particularly all-cause mortality and new onset acute HF. [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The most common causes of acute RHF are pulmonary embolism and acute myocardial infarction, mainly, but not exclusively, secondary to occlusion of the right coronary artery [ 12 ] (Table 1 ). Less frequently, acute RHF develops after cardiac surgery or LV assist device (LVAD) implantation [ 13 ].…”
Section: Aetiology and Epidemiology Of Right Ventricular Failurementioning
confidence: 99%